The Impact of Wage Increases on Job Satisfaction: Empirical Evidence and Theoretical Implications - Christian Grund; Dirk Sliwka (Institute for the Study of Labor (IZA), 2001)
The impact of wage increases on job satisfaction are explored. First, it is empirically established that current job satisfaction rises with absolute wage level as well as with wage increases. Second, a basic job satisfaction function is constructed based on the empirical results, and theoretical implications are analysed. It is shown that the myopic maximisation of such a function directly implies increasing and concave shaped age-earnings profiles.
Keywords: J30; M12; J28; 330; Job satisfaction; wage increases; habit formation; age-earnings profiles; Arbeitszufriedenheit; Lohn; Erwerbsverlauf; Schätzung; Deutschland